ANALYSIS THE EFFECTIVENESS OF MANAGING STATE-OWNED ASSETS USING SAKTI (Sistem Aplikasi Keuangan Tingkat Instansi) at BALAI BESAR PELAKSANAAN JALAN NASIONAL JAWA TENGAH - D. I. YOGYAKARTA - Aurelia, Elisabeth Nadine; Marliyati; Raharjo, Suko (Politeknik Negeri Semarang, 2025)
State-owned assets under the management of ministries or government institutions must be managed in an effective and efficient way. The effectiveness of state-owned assets management is expected to positively impact the performance, particularly in supporting operational activities that contribute to the implementation of public welfare programs. This study research is discussing about management procedures of state-owned assets specifically fixed asset classification using the SAKTI (Sistem Aplikasi Keuangan Tingkat Instansi), the obstacles encountered during implementation, also evaluates the effectiveness of state-owned assets management through an internal control system assessment and an evaluation of officer abilities to applicable regulations. The research employs a descriptive method, with data collected through questionnaires, observations, and documentation. The findings indicate that the state-owned assets management specifically fixed asset classification using the SAKTI (Sistem Aplikasi Keuangan Tingkat Instansi) has been conducted effectively, although certain aspects remain that require further improvement.